SOSIALISASI PERBANKAN SYARIAH TERHADAP SISWA YAYASAN SEKOLAH ALAM TUNAS MULIA BANTAR GEBANG - Ferda Yani Harahap; Emy Syariah; Rafika Rahmawati; Rizal Fahlevi (Al-Ihsan: Journal of Community Development in Islamic Studies, 2022)
One of the objectives of establishing Islamic banking is to support the implementation of national development and equitable distribution of people’s welfare. Officially, the Indonesian government has supported the existence of Islamic banking in Indonesian based on the law on Islamic banking. Islamic bank is bank that carry out activities based on sharia but there is still many who think Islamic bank are the same as conventional bank. Therefore, this community service aims to introduce Islamic banking systems, service principles and products. The method used in devotion to these students is in the form of counseling or socialization to the students of tunas mulia bantar gebang with the results that students have understood the basics of Islamic banking, through the interaction of questions and answers that the speaker has conveyed, where the questions asked can be answered properly.